Tissue-specificity of proteoglycans expression in different cancers - A. V. Suhovskih; E. V. Grigor’eva (Успехи молекулярной онкологии, 2016)
Background. Proteoglycans (PGs) are complex glycosylated molecules playing an important role in cell-cell and cell-matrix interactions and signaling. Expression of PGs and their expression pattern change considerably during malignant transformation of mammalian cells and tissues.Objective. The aim of our work was to investigate tissue-specificity of main PGs expression (glypican-1, perlecan, syndecan-1, aggrecan, versican, CSPG4/NG2, brevican, decorin, lumican) in normal cells (fibroblasts and normal epithelial prostate cells PNT2) and in different human cancer cell lines (prostate, breast, lung, brain, kidney). Expression patterns of main PGs were determined in these cells using reverse transcription polymerase chain reaction analysis and immunocytochemical staining.Results. It was shown that fibroblasts actively expressed PGs, and PNT2 cells had lower (5–6-fold) expression levels of a limited set of PG. In different cancer cell lines, overall transcriptional activities of PGs varied up to 10-fold, although their expression patterns had tissue-specific properties (for example, expression of syndecan-1 is more specific for prostate cancer cells, while perlecan is typical for lung cancer cell lines).Conclusions. Along with this, variability of the PG expression patterns in cell lines of the same tissue of origin was shown, suggesting a possible contribution of the variable PGs expression to intratumoural heterogeneity of cancer cells and their potential as perspective biomarker (s) for personalised cancer diagnostics.